Management Governance of Fish Landing in Fish Landing Officer (PPI) Gorontalo City, Gorontalo. - Regil Kentaurus Harryes; Laksmi Sulmartiwi (Universitas Airlangga, 2019)
Port infrastructure development is the main role to expand fishery. Therefore, Indonesian government pays attention in sailing products, where establishing fish market leads the appropriate program of government. And, Gorontalo is one of city with a coastal area and estuary with a fish landing and marketing site or Pangkalan Pendaratan Ikan (PPI). The Field Work Practice was held at Gorontalo City, District Hulondhalangi, Under the Guidance of the Department of Marine and Fisheries Gorontalo City Gorontalo province for thirty-six days from the date of January 18 to February 22. The results showed in this field practice is the flow of fish landing on PPI Gorontalo city has a shortage in the recording process and the results are less comprehensive infrastructure, the PPI Gorontalo city, there are 3 kinds of models of marketing channels.